Habitat and geochemical characterization of living planktonic foraminifera in the Caribbean - Jentzen, Anna (2016)
Planktonic foraminifera are unicellular organisms that precipitate their calcite tests from the seawater in which they live. The distribution patterns of species, as well as the trace elemental and isotopic composition of the tests, reflect the environmental conditions of the ambient seawater. Thus, fossil tests of planktonic foraminifera from sediments are widely used to reconstruct past ocean temperature and salinity variations. Studies on living planktonic foraminifera collected under natural conditions are essential for the interpretation of fossil data assessing the relationship between living specimens and in-situ ocean parameters. This study focused on the habitat patterns of tropical and subtropical living foraminifera and the isotopic (δ18O and δ13C) and Mg/Ca compositions of their tests. Plankton net samples were collected from the surface to a maximum 400 m water depth in the Caribbean Sea, Gulf of Mexico, Florida Straits and Santaren Channel. The data of living specimens were related to ambient seawater conditions (temperature, salinity, chlorophyll concentration and δ18O) and compared to fossil tests retrieved from the underlying surface sediments. Planktonforaminiferen sind einzellige Lebewesen, die ein Gehäuse aus Kalzit bilden. Sowohl die Artenverteilung im Ozean als auch die Zusammensetzung der stabilen Isotope und Spurenelemente in den Gehäusen reflektieren die Umweltparameter im umgebenden Meerwasser. Aus diesem Grund werden fossile Planktonforaminiferen aus Sedimenten weltweit genutzt, um Temperatur- und Salinitäts-Schwankungen der Ozeane in der geologischen Vergangenheit zu rekonstruieren. Untersuchungen an lebenden Planktonforaminiferen, welche in ihrer natürlichen Umgebung gesammelt werden, sind essenziell für die Interpretation fossiler Daten, da sie den Zusammenhang zwischen lebenden Foraminiferen und in-situ gemessenen Umweltparametern widerspiegeln. Diese Studie befasst sich mit den Habitaten von lebenden tropischen und subtropischen Foraminiferen und untersucht die stabilen Isotopen ...